Sites governamentais e mecanismos de informação, transparência e participação - Silva, Joscimar Souza (2014)
This paper analysis the reflections about information, transparency and political participation in digital spaces by political institutions. The analysis is focusing in the egovernmental sites in the subnational states, adding empirical data to a theoretical discussion on the relations of state and government on the internet, thinking of the institutions of the Brazilian states units and the prominent actors in this board debate about the relationship between the internet and politics. The theoretical discussion is fundamental in structuring this analysis. We attempted to use empirical data for the purpose of finding the quantitative and qualitative use of the internet by subnational governments in Brazil and to test some real applications worldwide network of computers for management of the state and the expansion of democratic spaces institutionalized. We take as considerations that internet use by state and subnational governments is still an open issue for further reflection and that is practical application at the same time can contribute to the change of an entire state structure and expand democratic spaces still suffers from problems of institutional junctures, with the role of political actors and external issues, such as the democratization of technological and the political culture.